The Role of Tadwīn Hadith in the Development of Islamic Historiography - Tri Nurcahyani Sari Tanjung; Zulfi Fadhlurrahman (Seutia Hukamaa Cendekia, 2025)
This study discusses the contribution of the method of codification (tadwīn) of hadith to the development of early Islamic historiography. The relationship between the tradition of hadith and history is often viewed in a dichotomous manner; hadith is considered a strictly theological-juridical domain, while history (tārikh) is considered a loose narrative. This research aims to deconstruct this view by analyzing the crucial role of hadith codification (tadwīn) in shaping Islamic historiographic methodology. Using qualitative research methods with a descriptive-analytical approach, this study traces the epistemological transition from oral to written traditions in the early centuries of the Hijri. This study outlines four main contributions, namely: (1) hadith as a source of historical information, (2) hadith collection methods that influence historical data tracking techniques, (3) sanad and matan criticism methods that introduce the principle of validation in historical writing, and (4) methods of compiling hadith books that form the structure of historiographic writing, such as the use of tabaqāt approaches and biographies of figures. This paper shows that the methods in the study of hadith have provided a strong epistemological foundation for the Islamic historiographic tradition, especially in the aspects of source accuracy and systematics in the preparation of historical narratives.